Pengaruh Financial Knowledge dan Financial Self-Efficacy terhadap Financial Management Behavior pada Pelaku UMK - Mutiara Nur Ihsan; Dede Kurnia; Azizah Fauziyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of financial knowledge and financial self-efficacy on financial management behavior among MSME actors in Lamajang Village. Although MSMEs in the region continue to grow, most business actors are still oriented toward short-term profits that tend to be consumptive, so that financial management has not become a top priority. In fact, financial management skills are a crucial factor for business sustainability and success. This study uses a quantitative approach with a descriptive method. The research sample consists of 118 SME operators engaged in the culinary, agribusiness, handicraft, and other sectors. Data were collected through questionnaires and analyzed using descriptive statistics, classical assumption tests, simple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that both financial knowledge and financial self-efficacy have a positive and significant impact on financial management behavior, both partially and simultaneously. These findings suggest that the better the financial understanding and self-confidence of SME operators, the more optimal their financial management behavior, including in terms of planning, cash flow control, risk management, and transaction recording. Therefore, efforts to develop SMEs should not only focus on improving financial literacy but also on strengthening psychological aspects to foster confidence in making financial decisions.